In Situ Electrophilic Activation of Hydrogen Peroxide for Catalytic Asymmetric α-Hydroxylation of 3-Substituted Oxindoles - Ohmatsu, Kohsuke; Ando, Yuichiro; Ooi, Takashi (Synlett, 2017)
Peroxy trichloroacetimidic acid, in situ generated from aqueous hydrogen peroxide and trichloroacetonitrile, was found to act as a competent electrophilic oxygenating agent for the direct α-hydroxylation of oxindoles. The use of chiral 1,2,3-triazolium salt as a phase-transfer catalyst enabled rigorous absolute stereocontrol in the carbon–oxygen bond-forming reaction. The present study provides a new, yet practical method for straightforward access to optically active α-hydroxycarbonyl compounds.
Keywords: hydroxylation; carbonyl compound; hydrogen peroxide; imidic acid; oxindole; chiral ion pair; 1,2,3-triazolium ion